ANALISIS SPASIAL LAHAN PERTANIAN PANGAN BERKELANJUTAN (LP2B) DI KABUPATEN PESAWARAN - Pratama, Agung; Amin, Mohamad; Asmara, Sandi; Rosadi, Bustomi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2018)
ABSTRACT  Land is the main factor in developing agriculture.  The increase of population’s number and economy activity, give impact to land’s needs.  This should trigger land conversion happen.  Land conversion would be a problem if that happens on productive agricultural land.  According to BPS Pesawaran, that every years the harvested area of rice crops decreased in Pesawaran regency.  Lahan Pertanian Pangan Berkelanjutan (LP2B) is the government’s effort in protecting and overcome land conversion of food agricultural land.The purpose of this research was to analyze the potential of Lahan Pertanian Pangan Berkelanjutan (LP2B) and Lahan Cadangan Pangan Berkelanjutan (LCP2B) in Pesawaran regency.  The decree of LP2B and LCP2B refers to Constitution number 41 in 2009 about Perlindungan Lahan Pertanian Pangan Berkelanjutan (UU PLPPB).The potency of LP2B in Pesawaran regency is as large as the total potency’s wide of Lahan Pertanian Pangan Berkelanjutan (LP2B) in Pesawaran regency that is 10.236,49 Ha, which is consisted as potency of Lahan Cadangan Pertanian Pangan Berkelanjutan (LCP2B) of 1.294,06 Ha. Keywords : Land conversion, LP2B, LCP2B, and Pesawaran Regency.